Feasibility of using Static-Cast Concrete Transmission Poles fully reinforced with glass-fibre reinforced polymer bars and stirrups: A case study - Hassan Ahmadi; Milad Shakiba; Seyed Mohammad Reza Mortazavi; Milad Bazli; Zahir Azimi (Case Studies in Construction Materials, 2023)
The findings of cantilever beam bending tests conducted on a series of full-scale glass fibre-reinforced polymer (GFRP) and steel-reinforced concrete utility poles are presented. The poles were reinforced by (i) longitudinal steel bars and steel stirrups (ii) longitudinal GFRP bars and steel stirrups, and (iii) longitudinal GFRP bars and GFRP stirrups. Crack initiation and propagation as well as load carrying capacity and free end deflections of GFRP reinforced poles were obtained and compared with their counterpart steel reinforced poles. Based on the results all longitudinal GFRP reinforced poles have shown higher load-carrying capacity than that of steel reinforced poles, while due to the lower stiffness of GFRP bars in comparison to steel bars, at a certain load, higher free-end deflections were observed in GFRP reinforced poles. However, the permanent deformation of GFRP-reinforced poles was small. Furthermore, comparable results obtained for poles reinforced with GFRP stirrups than those of poles reinforced with steel stirrups, showed that GFRP stirrups could also be used safely instead of steel stirrups. However, due to the low elastic modulus, GFRP-reinforced poles likely fail to satisfy the deflection criterion specified in some standards. But, if adequate stiffness is provided for GFRP-reinforced concrete poles to satisfy the deflection criterion, due to the vulnerability of steel-reinforced utility poles when subjected to corrosive environments, using fully GFRP-reinforced concrete poles could be a feasible option.